2016
DOI: 10.1016/j.matchar.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sigma and chi phases in duplex stainless steels

Abstract: The aim of this work is to find out the most suitable method for detecting and analyzing accurately the formation conditions of secondary phases, particularly Sigma-phase (σ-phase) and Chiphase (χ-phase) in duplex stainless steels (UNS S32205 and UNS S32750). The microstructure was characterized after a solution annealing at 1080oC followed by an isothermal heating at 830oC for different time ranges, ranging from 1 minute to 9 hours, in order to enlighten the controversial point concerning the mechanism of χ-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
64
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(77 citation statements)
references
References 20 publications
11
64
0
2
Order By: Relevance
“…Cieslak et al [26] found that χ phase can form in the solid state during high cooling rates, which occur in welds from 316 austenitic steel. Additionally, similar morphology of χ phase as in alloy 2, was reported by Llorca-Isern et al [27]. During precipitation, the χ phase consumed Cr and Mo, which causes the surrounding areas to be depleted in these elements.…”
Section: Microstructuresupporting
confidence: 83%
“…Cieslak et al [26] found that χ phase can form in the solid state during high cooling rates, which occur in welds from 316 austenitic steel. Additionally, similar morphology of χ phase as in alloy 2, was reported by Llorca-Isern et al [27]. During precipitation, the χ phase consumed Cr and Mo, which causes the surrounding areas to be depleted in these elements.…”
Section: Microstructuresupporting
confidence: 83%
“…In this work, however, the presence of the chi phase at temperatures between 850 °C and 950 °C was not identified. This behavior could be attributed to the solubilization treatment before isothermal aging, which would cause the development of different microstructural conditions (grain size, and different morphology of the austenite and ferrite clusters), leading to changes in the kinetics 7 and favoring rapid consumption of the chi phase. Wong et al 15 showed that dissolution of the sigma phase could occur at 860 to 910 °C and at 910 to 930 °C under continuous heating.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Differences in the solution-treated state of the non-aged metal alter the duration of each transformation mechanism, due to changes in the initial grain size and the dislocations density of the base metal. The initial solutiontreated condition of the base metal plays a very important role in the kinetic behavior of the precipitation 7,16 .…”
Section: Quantitative Analysismentioning
confidence: 99%
See 2 more Smart Citations